The Effect of Sorting Waste Saving Gold on Financial Independence and Sustainable Behavior Mediated by Financial Inclusion - Eka Pebriansyah; Eric Harianto; Jocelyn Belle Setiawan; Yanti Octaviani (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Indonesia faces waste management and financial inclusion challenges. Pegadaian’s Sorting Waste, Saving Gold program addresses both by converting sorted inorganic waste into digital gold savings that promote sustainability and financial inclusion. This study examines the program’s effects on financial independence and sustainable behavior, with financial inclusion as a mediating variable. A quantitative explanatory approach was employed through a survey of 2,173 active participants who had joined the program for at least three months and maintained active gold savings accounts. Data were analyzed using partial least squares structural equation modeling. Findings reveal that the program has a positive and significant effect on financial inclusion, financial independence, and sustainable behavior. Financial inclusion plays a strong mediating role, especially in the relationship with financial independence, where the indirect effect substantially outweighs the direct effect. For sustainable behavior, the program exerts a robust direct influence that is further enhanced through financial inclusion. The program proves that linking waste management to simple financial tools can broaden inclusion, empower people economically, and build lasting eco-friendly routines. Pegadaian should scale waste bank partnerships, upgrade digital features, and add basic financial education for stronger, sustained impact.